Increased in-stent stenosis in ApoE knockout mice: insights from a novel mouse model of balloon angioplasty and stenting. - Ali, Z; Alp, N; Lupton, H; Arnold, N; Bannister, T; Hu, Y; Mussa, S; Wheatcroft, M; Greaves, D; Gunn, J; Channon, K (2007)
OBJECTIVE: We aimed to develop and validate a model of angioplasty and stenting in mice that would allow investigation of the response to stent injury using genetically modified mouse strains. METHODS AND RESULTS: Aortic segments from either C57BL/6 wild-type or atherosclerotic ApoE-KO mice underwent balloon angioplasty alone or balloon angioplasty and stenting with a 1.25x2.5 mm stainless steel stent. Vessels were carotid-interposition grafted into genetically identical littermate recipients and harvested at 1, 7, 14, or 28 days. In wild-type mice, stenting generated an inflammatory vascular injury response between days 1 to 7, leading to the development of neointimal hyperplasia by day 14, which further increased in area by day 28 leading to the development of in-stent stenosis. Uninjured vessels and vessels injured by balloon angioplasty alone developed minimal neointimal hyperplasia. In stented ApoE-KO mice, neointimal area at 28 days was 30% greater compared with wild-type mice. CONCLUSIONS: By reproducing important features of human stenting in atherosclerotic mice, we provide the potential to investigate molecular pathways and evaluate novel therapeutic targets for stent injury and restenosis.